Mixed Pellet and Forage Diet in Growing Rabbits: Effect of Ipomoae batatas on Growth and Health Performance - Soro, Ouation Souleymane; Kadjo, Vincent; Yao, Koffi Sylvanus Aubert; Kimse, Moussa (International Journal of Applied Sciences and Biotechnology, 2023)
The aim of this work is to test the effect of green forage Ipomoea batatas on young rabbit (Oryctolagus cuniculus) digestive health and growing performance. Two group (T and I) of 15 rabbits were made. These animals were weaned at 35 days of age and slaughtered at 70 days. The mean weight per group was 500 ± 20 g. Control group T was feed only with industrial pelleted Ivograin®. Experimental group I was feed with the same pelleted diet and green forage I. batatas in the cage. Results showed that the growing performances in group I were lower than control. Group I daily gain was 0.89g lower than T (P<0.01). Fed intakes was 1.05 times lower with forage than control (P<0.01). For sanitary risk index (mortality + morbidity) was 2 part higher in group I than control (14 vs 7, P<0.01). However, the nutrient digestibility was higher with I. batatas group than control. Digestibility of DM, OM, CP, NDF, ADF and Hc was 26.68, 23.43, 9.67, 18.56, 18.74 and 16.46 respectively higher with group I than control (P<0.05). We can conclude that, associate green forage I. batatas with pelleted diet was not increased the young rabbit growing performances and health except nutrients digestibility. Int. J. Appl. Sci. Biotechnol. Vol 11(3): 123-127.